Las sphragídes en Metamorfosis 15 y en Amores 1.15: el anuncio de la inmortalidad y la vida eterna (Argos, 2024)
The present work intends to analyze the reason for the immortality of the poet inthe sphragídes of Metamorphosis 15 (Ov. Met. 15. 861-879) and Amores 1.15(Ov. Am. 1.15. 1-42) and the way in which Ovid uses his literary production toconsciously insert himself into the Greco-Latin canon. The complex framework ofthe works and the mention of authors who have already been canonized, as wellas the correlates with other sources, serve to announce his immortality thanks towriting, which will be embodied in its metaphorical apotheosis through reading bythe populus.